Preparatory training attenuates drastic response of the insulin-like growth factor binding protein 1 at the point of maximal oxygen consumption in handball players - Olgica Nedić; Miloš Šunderić; Goran Miljuš; Zoran Valdevit; Vladimir Jakovljević; Marija Glibetić; Vesna Vučić (Elsevier, 2017)
Background: Intensive exercise changes physiological need for glucose and several biochemical pathways responsible for its metabolism response. Among them are those which involve insulin, insulin-like growth factor (IGF-1), and IGF-binding proteins (IGFBPs). Different types and degrees of exercise, as well as an athlete's fitness, may induce a range of responses regarding concentrations and time needed for the alteration. The idea of the work was to find out whether and how insulin/IGF axis responds to additional physical activity in the already trained subjects and if so, is the adaptation potentially beneficial from the aspect of metabolic control. Methods: The effect of 4-week intensive training on campus (preparatory training) on the levels of insulin, IGF-1, and IGFBPs during maximal progressive exercise test (MPET) on a treadmill was compared to the results obtained during MPET conducted after a regular training season of a female elite handball team (n = 17, age: 17 ± 1 years, height: 171 ± 8 cm, weight: 65 ± 8 kg, body mass index: 22 ± 1 kg/m2 at the beginning of the study; there were no significant changes at the end). Serum samples were obtained from players immediately before the test (basal), at the end of the test after reaching the point of maximal oxygen consumption (VO2max), and after recovery. Results: The concentration of insulin decreased at VO2max, but remained higher in players after preparatory training (12.2 ± 2.5 mU/L vs. 8.9 ± 4.4 mU/L, p = 0.049). The level of IGFBP-1 decreased in players at VO2max in either case of training, but it remained much higher in tests performed after the preparatory regime than before (p = 0.029). Concentrations of IGF-1, IGFBP-2, -3, and -4 did not change significantly. Conclusion: The inverse relation between insulin and IGFBP-1 was lost during MPET, as these 2 molecules changed in the same direction. The results obtained suggest less severe stress-induced depression of insulin and IGFBP-1 after preparatory training. But another metabolic mechanism cannot be excluded, and that is potentially impaired insulin sensitivity resulting in higher level of IGFBP-1.